Are Anesthesiology Providers Good Guessers? Heart Rate and Oxygen Saturation Estimation in a Simulation Setting - Efrain Riveros Perez; Enoe Jimenez; Camila Albo; Yashi Sanghvi; Nianlan Yang; Alexander Rocuts (Anesthesiology Research and Practice)
Background. Anesthesia providers may need to interpret the output of vital sign monitors based on auditory cues, in the context of multitasking in the operating room. This study aims to evaluate the ability of different anesthesia providers to estimate heart rate and oxygen saturation in a simulation setting. Methods. Sixty anesthesia providers (residents, nurse anesthetics, and anesthesiologists) were studied. Four scenarios were arranged in a simulation context. Two baseline scenarios with and without waveform visual aid, and two scenarios with variation of heart rate and/or oxygen saturation were used to assess the accuracy of the estimation made by the participants. Results. When the accurate threshold for the heart rate was set at less than 5 beats per minute, the providers only had a correct estimation at two baseline settings with visual aids (p=0.22 and 0.2237). Anesthesia providers tend to underestimate the heart rate when it increases. Providers failed to accurately estimate oxygen saturation with or without visual aid (p=0.0276 and 0.0105, respectively). Change in recording settings significantly affected the accuracy of heart rate estimation (p<0.0001), and different experience levels affected the estimation accuracy (p=0.041). Conclusion. The ability of anesthesia providers with different levels of experience to assess baseline and variations of heart rate and oxygen saturation is unsatisfactory, especially when oxygen desaturation and bradycardia coexist, and when the subject has less years of experience.